Nanostructured Photocatalysts Advanced Functional Materials - Yamashita, Hiromi; Li, Hexing (Nanostructure Science and Technology,, 2016)
While books on semiconductor TiO2 photocatalysis are legion, nanostructured controlled photocatalysts are attractive beyond standard semiconductors, and this book is devoted to the many novel uses of advanced TiO2 and MOF-based photocatalysts. Details on synthesis, characterization, and reaction applications of nanostructured photocatalysts are summarized. Other new materials discussed in this book are Bi- W- oxides, metal complexes, and unique porous materials. This book contains methods of preparation and characterization of unique nanostructured photocatalysts, and details about their catalytic action. Contributors to this volume are leading Asian researchers in Photocatalysis. It will appeal to researchers wishing to know how to design new types of photocatalysts with controlled nanostructures.